The Effectiveness of Collaborative Problem-solving Using Decision-making Problems to Improve the Pre-service Physics Teachers’ Critical Thinking Skills - Yusal, Yulianti; Suhandi, Andi; Setiawan, Wawan; Kaniawati, Ida (Jurnal Pendidikan Fisika, 2021)
Research on the effectiveness of collaborative problem-solving using decision-making problems in improving pre-service physics  teachers’ thinking skills has been carried out. This research aims to find out the effectiveness of the application of collaborative problem-solving using decision-making problems to improve the pre-service physics teachers’ critical thinking skills. The method used was pre-experiment with one group pretest-posttest design. The research subjects were 76 pre-service physics teachers at a university in the city of Makassar, South Sulawesi. An essay test of critical thinking skills was employed to collect the data that 6 items. The results showed that after implementing collaborative problem-solving using decision-making problems, students' critical thinking skills increased to high category, and most of the students’ critical thinking skills improvements are also categorized as high. Thus, collaborative problem-solving using decision-making problems is effective to improve the pre-service physics teachers critical thinking skills.